O ensino de geometria projetiva na educação básica: uma proposta para apreensão do conhecimento do mundo tridimensional - Schmidt, Elvis (2015)
In search for a better representation of three-dimensional reality, non-Euclidean Geometries offer an alternative to the classic euclidianism and the Projective Geometry is one of the highlights. The purpose of this word is contribute to the assimilation of definitions such as perspective, projection, and the principle of duality, through illustrations. And, from important results as Desargues’ Theorem, Pappus’ Theorem and Pascal’s Theorem, we want to facilitate understanding and viewing some of the perspective techniques that can be adapted for use in classroom by Basic Education teachers. The application of a workshop of Projective Geometry in a class of 6th grade of elementary school and the evaluation of the results revealed that the theme can be developed in a promising way with students in basic education, getting a better comprehension of the real object and associating it to the mathematical content involved.